Assessment of on-Farm Management And Associated Knowledge of Agro-Biodiversity In Climate Smart Viilages of Nawalpur District in Nepal (SAARC Journal of Agriculture, 2021)
The study was conducted in Nawalpur district of Nepal to assess status of on-farm management and associated knowledge of agrobiodiversity. Further, this study identified the farmers perception and their local interventions in on-farm agrobiodiversity conservation and management. The snowball and simple random sampling technique were used to identify the farmers practicing on-farm management and those who do not respectively. The pretested questionnaire was administered to 100 farmers of two villages, 50 from each village, from 2nd to 5th March 2018. Descriptive and analytical statistical tools were used to determine and compare the factors associated with on-farm management of agrobiodiversity. The study revealed that out of 98.0% of the respondents practicing on-farm management, almost all had home garden followed by 74.50% involved in value addition, 59.20% agrodiversity fair, 55.10% Community Biodiversity Management (CBM) and 36.10% travelling seminar. There was a significant relation between the type of the farming system and CBM (at p 0.00), travelling seminar (at p 0.043) and value addition (at p 0.036). The majority of respondents were commercial farmers, they sell what they produce for livelihood, and were practicing on-farm management of agrobiodiversity. Different means of information were used, where major being the information given by the respondents. Lack of government’s technical support and information on Community based Biodiversity Management (CBD), were the major reasons for farmers for not being able to acquaint with it, and practice it on local conditions. Proper training and awareness, agricultural promotion programs are the absolute imperative to improve on-farm agrobiodiversity conservation and management status.SAARC J. Agric., 19(1): 259-268 (2021)